An Exploratory Study for Opening Accounting Undergraduate Program in Saudi Arabia: The Stakeholders’ Perception & Need Analysis - Shahid, Dr. Humera; Alexander, Dr Asha; Mohammed Abdalla, Dr. Tayfour Abdalla (Advances in Social Sciences Research Journal, 2018)
Purpose: Educational institutions are transforming their programs’ learning outcomes from theory based to mixed based consisting of theory, practical and technology in order to equip graduates with skills that are highly demanded by industry due to digital transformation especially in professions like accounting and finance. This study aims to conduct a need analysis in order to get stakeholders’ perception for opening of IT based undergraduate accounting program in the eastern province of the Kingdom of Saudi Arabia in order to provide IT skilled accounting professional to Industry. Design/methodology/approach: There is use of both qualitative and quantitative data in a manner that enables insight to be mutually illuminating. Principal Component Analysis (PCA) was carried out in order to group the 15 manifest variables into few latent variables. Factor analysis has reduced variables to two factors and analysis of variance was applied to test the main differences between groups. Findings: Findings have shown a favorable perception of the stakeholders for opening of undergraduate Accounting program focusing on knowledge, cognitive, interpersonal as well as technology based skills. Industry experts has shown a positive attitude about demand for students passing out from such degree. Originality/value: This study has provided an insight about the rising importance of accounting programs in developing country for researchers, educators and practitioners. This could be explored by further research to set up specific initiatives aimed at enhancing those aspects of the accounting program that are overshadowed or undermined in curriculum.